-2x-3y=-7 y=6x-11 If someone answers this and shows work I will give Brainlyest

Question

-2x-3y=-7
y=6x-11
If someone answers this and shows work I will give Brainlyest

in progress 0
Latifah 6 months 2021-08-04T08:44:33+00:00 2 Answers 4 views 0

Answers ( )

    0
    2021-08-04T08:46:02+00:00

    Answer:

    x = 2, y = 1

    Step-by-step explanation:

    We have a system of equations:

    -2x – 3y = -7

    y = 6x – 11

    Substitute the given value of y into the equation -2x – 3y = -7

    -2x – 3 * (6x – 11) = -7

    -20x = -7 – 33

    -20x = – 40

    x = 2

    Substitute the given value of x into the equation y = 6x – 11

    y = 6x – 11

    y = 6 * 2 – 11

    y = 1

    0
    2021-08-04T08:46:15+00:00

    Answer:

    x = 2

    y = 1

    Step-by-step explanation:

    -2x-3y=-7, y=6x-11

    -2x – 3(6x – 11) = -7

    -2x – 18x + 33 = -7

    -2x – 18x = -40

    -20x = -40

    x = 2

    y = 6(2) – 11

    y = 12 – 11

    y = 1

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )